IMPLEMENTASI PENDIDIKANKESEHATAN SEBAGAI SEBUAH UPAYA UNTUK MENINGKATKAN PENGETAHUAN DAN PERILAKU IBU DALAM MEMBERIKAN ASI EKSKLUSIF - Kurniawati, Dini (Jurnal Pengembangan Pendidikan, 2012)
Abstract. In general practice of giving exclusive breast-feeding still low fromachievement target although various studies have shows the benefit of exclusivebreast-feeding to the babyâs health haveÂ been done. To achieve this, there needs to be knowledge forÂ mothersÂ about exclusive breast-feedingÂ because motherâs knowledge is very important domain in shaping thebehavior ofÂ giving exclusivebreast-feeding. The purpose of this study was to know the influence of healtheducation on motherâs knowledge and behavior in giving exclusive breast-feeding.Study Design is one pretest posttest designs. Techniques used in taking samplesis purposive sampling with a sample size of 30 people. Based o the result ofdata analysis with sign test techniques is obtained p-value /Asym sig =0,000< Î± (0,05) so it can be concluded that there is influence betweenÂ Â Â health education on motherâs knowledge andbehavior in giving exclusive breast-feeding. To improve the achievement ofgiving exclusive breast-feeding, they need to have adequate health educationand to increase knowledge. Patientâs knowledge about exclusive breast-feedingwill shape motherâs attitudes to do exclusive breast-feeding. In theory,changes in behavior or adopt new behaviors, follow the steps mentioned above,are through the process: knowledge,attitude,practice.Â Key words: health education, knowledge, behavior,exclusive breast-feeding